Quid pro quo: Against Which Contractual Remedies is the Exception of Non-Performance Effective? - Castro Zurita, Felipe (Iuris Dictio, 2023)
There are several contractual remedies for the pathology of non-performance, such as termination, enforcement, or compensation for damages. Moreover, there is a defense against reciprocal breach, known as exception of non-performance. This figure, traditionally understood, prevents a contracting party from requiring performance if it has not complied with the agreement either or is not ready to do so. The present study observes the possibility of presenting an exception of non-performance to neutralize a claim for damages and a termination claim. The nature and foundation of the exception of non-performance was observed, to demonstrate that in cases of reciprocal breach it is possible to terminate the contract, but a party cannot request a compensation for damages due to non-performance.